Has the web promoted diversity? Ownership concentration and online news traffic in Greece - Spyridou, Lia Paschalia; Manavopoulos, Vasilis (My University, 2025)
News media concentration raises concerns associated with the power to influence policy, political developments and public debates. Low entry-barriers and reduced production and distribution costs in the web era promised a more pluralistic media landscape, which has thus far failed to materialise as reputational, technical and financial resources tend to confer cumulative advantages for larger and more established media organisations. In this study, we examine economic and ownership concentration for the 80 most popular news websites in Greece. Contrary to the traditional news media industry of the country and its European counterparts we find the Greek online news market to exhibit relatively low levels of concentration. Deep distrust towards the media along with an emerging and populous web-native news market can explain the findings. However, we find that in terms of ownership type, a considerable amount of traffic is directed toward websites owned by conglomerate companies whose economic interests lie outside the media industry. Specifically, websites belonging to traditional media houses share about one third of traffic and an emergent new type of conglomerate ownership coming from web-native media captures about another third. The findings raise concerns regarding the large ‘market share’ controlled by media owned by conglomerate companies suggesting that the digital landscape can also facilitate media capture despite hopes of the opposite effect.
Keywords: ownership form; web-native media; Media concentration; media ownership; news referrals; news traffic; trust in news